CHARACTERIZATION OF HEART SIZE AND BLOOD PRESSURE IN THE VITAMIN D RECEPTOR KNOCKOUT MOUSE - SIMPSON, ROBERT U. (2006)
Our previous studies showed vitamin D deficiency results in increased cardiac contractility, hypertrophy and fibrosis and has profound effects on heart proteomics, structure and function in rat. In this study we found that the heart in vitamin D receptor knockout (VDR-KO) mice is hypertrophied. Six homozygous VDR knockout (−/−), 6 wild type (+/+) and 6 heterozygous (+/−) mice were fed a diet containing 2% Ca, 1.25% P and 20% lactose to maintain normal blood calcium and phosphate levels for 12 months. Tail-cuff blood pressure was performed on all mice. Blood pressure determinations showed no differences in systolic or mean blood pressure in WT (+/+), KO (−/−) or HETERO (+/−) mice at 3 and 6 months. However, decreased systolic BP in the KO mice relative to WT at 9 months of age was observed. ECG analysis showed no significant differences in the intact KO, HETERO or WT mice. The mice were killed at 12 months. Heart wt/body wt ratio was 41% (p<.003) greater in the KO mice vs. WT and HETERO was 19% (p<.05) increased vs. WT. Other VDR-KO tissues did not display hypertrophy. Cross sectional and longitudinal analysis of the heart myofibrils showed highly significant cellular hypertrophy in VDR-KO mice. Trichrome staining of heart tissue showed marked increase in fibrotic lesions in the KO mice. Analysis of plasma renin activity, angiotensin II (AII) and aldosterone levels showed elevated but not significantly different renin activity in KO vs. WT and no significant differences in AII or aldosterone levels. Our data do not support the concept that the renin-angiotensin system or hypertension are the factors that elicit these changes. Data presented here reveal that ablation of the VDR signaling system results in profound changes in heart structure. We propose that calcitriol acts directly on the heart as a tranquilizer by blunting cardiomyocyte hypertrophy.